Why some football referees engage in match-fixing? A sociological explanation of the influence of social structures - Moriconi, M.; Cima, C. (International Journal of Sport Policy and Politics, 2021)
This article shows how governance failures within sport governing bodies promote opportunity structures for the manipulation of competitions. Based on a triangulation of qualitative methods, including interviews with key sport actors, the paper describes the structural constraints by which football referees may accept to perform their role while favouring one of the teams and, consequently, to apply the regulations with partiality and injustice. Cultural and relational constraints are presented and explained. Among the cultural ones, the work identifies a selective application of formal rules, the normalisation of abnormality, and the subsequent formalisation of abnormality. At the relational level, direct asymmetric relationships, indirect asymmetric relationships, and symmetric relationships are discussed. Since wrongdoing and the manipulation of competitions are understood by some referees as a necessary condition to progress in their career or to keep it ongoing, findings reinforce the importance of paying attention to the theories of social structure, and at the meso level, to explain the phenomenon of match fixing. Empirical and theoretical contributions support the need for developing anti-match fixing policies according to the social contexts in which sports actors are involved. It also opens a line of debate on the need to control externally and independently the Sport Governing Bodies.